Interview with Attilio Mastrocinque: the material culture as source for the investigation about the religious practices and conceptions in Antiquity - Mastrocinque, Attilio (Romanitas - Revista de Estudos Grecolatinos, 2017)
Interview with Attilio Mastrocinque.